STUDI PENYEDIAAN PAKAN PADA PETERNAKAN DOMBA RAKYAT DI DAERAH SUB TROPIS - ., Sujono; Hidayati, Asmah (Jurnal Gamma, 2012)
Studi Penyediaan Pakan Pada Peternakan Domba Rakyat di Daerah Sub TropisSujono1 & Asmah Hidayati21&2 Staf Pengajar Produksi Ternak, Fakultas Pertanian PeternakanUniversitas Muhammadiyah Malang e-mail: 1)sujono_umm64@yahoo.com, 2)asmah.hidayati@yahoo.comABSTRACTThe objection of this research was to compare the activity of feedstuff preparation for sheep by the seasons between the tropics and sub tropics area.Survey method was used for search the data and observation with interview technique as the way for take data more accurately. Interview were walked out in the rural of Palmerston north (sub tropics area) and Malang District (tropics area).The kind of feedstuff in the two area were same, namely forages and concentrate. The kind of forages and concentrate source were difference based on the seasons. The source of the feedstuff, technique of saving and technology for increase the feedstuff quality more complex and variation in tropics than in sub tropics area. The differences was caused by the farm management, area of paddock and human resources which were having in the two regions.Key words ; sources, kind and technology of feedstuff